2021
DOI: 10.1111/ijn.12949
|View full text |Cite
|
Sign up to set email alerts
|

Distress in the context of cancer and chemotherapy: A mixed‐method study

Abstract: Background There are controversial results about the effects of cancer and chemotherapy on the perception of distress. Aims The purpose to the study is to explore the meaning of the distress experienced by patients with cancer and verify whether the cancer diagnosis, stage and receiving chemotherapy influence this experience. Design This is a mixed‐methods study with cancer patients. Methods Data were collected in 2018 using a phenomenological interview (n = 18) and one suffering inventory (n = 100). Qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…During this period, the country recorded the highest infection, hospitalization, and death rates associated with COVID-19, and the Brazilian health system collapsed [ 67 ]. This suspicion is supported by the findings of Brazilian authors who found, in 2018, low levels of distress in patients with indications for antineoplastic chemotherapy [ 10 ], as well as in a study that compared quality of life before and during the pandemic. They demonstrated that the rescheduling of treatment cycles in Brazil induced emotional imbalance due to the disturbing nature of waiting for treatment [ 68 ].…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…During this period, the country recorded the highest infection, hospitalization, and death rates associated with COVID-19, and the Brazilian health system collapsed [ 67 ]. This suspicion is supported by the findings of Brazilian authors who found, in 2018, low levels of distress in patients with indications for antineoplastic chemotherapy [ 10 ], as well as in a study that compared quality of life before and during the pandemic. They demonstrated that the rescheduling of treatment cycles in Brazil induced emotional imbalance due to the disturbing nature of waiting for treatment [ 68 ].…”
Section: Discussionmentioning
confidence: 60%
“…Based on the mean number of patients who received chemotherapy for the first time in the outpatient clinic in the previous 12 months, the sample size was calculated by using G-power software, adopting a power of the test of 80% and a level of significance of 5%. Following Kang’s recommendations [ 37 ] for controlling type I (false positive) and type II (false negative) errors, the calculation was performed a priori, and the power of the effect was determined based on a previous study with a similar methodological design [ 10 ]. The result was a sample of 91 patients who were considered to have borderline representativeness, between moderate and high, according to systematic review [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations